2021
DOI: 10.5551/jat.57083
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of the Direct Occluded Vessel Puncture Technique as a New Access Site for Complex Peripheral Artery Occlusive Disease

Abstract: This study aims to describe the feasibility and safety of direct occluded vessel puncture as a new access site for complex peripheral artery occlusive disease.Methods: Eleven consecutive patients with symptomatic peripheral artery disease underwent endovascular therapy using the direct occluded vessel puncture technique. The occluded vessel was punctured using a dedicated 20 G needle and the Hi-Torque Command 18 ST guidewire under duplex echo or fluoroscopic guidance, and a 6 Fr sheath was then inserted. Hemos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“… 1 , 2 Another report demonstrated that the EXOSEAL can be safely used for antegrade direct puncture of the patent SFA with ultrasound or fluoroscopic guidance. 3 Recently, Kawasaki et al 4 reported the use of the EXOSEAL for the occluded SFA, which required confirmation of the extravascular position of the indicator wire by fluoroscopy at the plug deployment. In our case, we accessed the femoral artery by palpation-guided puncture, and we did not notice the unintentional puncture of the proximal SFA.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Another report demonstrated that the EXOSEAL can be safely used for antegrade direct puncture of the patent SFA with ultrasound or fluoroscopic guidance. 3 Recently, Kawasaki et al 4 reported the use of the EXOSEAL for the occluded SFA, which required confirmation of the extravascular position of the indicator wire by fluoroscopy at the plug deployment. In our case, we accessed the femoral artery by palpation-guided puncture, and we did not notice the unintentional puncture of the proximal SFA.…”
Section: Discussionmentioning
confidence: 99%
“…Direct puncture of the occluded CFA could be an effective alternative measure to deal with this situation. Kawasaki et al reported on the efficacy of puncturing occluded vessels for peripheral vascular interventions (Kawasaki et al 2021 ). While ultrasound guidance was used in the present case for the vessel puncture, the puncture can be performed under fluoroscopy in a case of heavily calcified wall (Kawasaki et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%